Problem-Based Learning (PBL) in higher education: Literature review and practical implications for its implementation in the Dominican Republic - Orgaz Agüera, Francisco; Domínguez Valerio, Cándida María; Trinidad Domínguez, María Esther (LACCEI, 2025)
Problem-Based Learning (PBL) is an educational methodology focused on solving real-world problems, fostering interdisciplinarity, critical thinking, and active learning. This study conducts a systematic literature review on PBL in higher education, with an emphasis on its application in engineering and its integration with Education for Sustainable Development (ESD). The study identifies benefits such as the strengthening of technical and attitudinal competencies, but also challenges, including the need for teacher training and curriculum adaptation. Practical implications for its implementation in the Dominican Republic are proposed, including teacher training, interdisciplinarity in engineering education, and the establishment of partnerships with industry. The study concludes that PBL is a key tool for improving sustainability education in higher education, although further research is needed in the context of developing countries.